Use of urinary gram stain for detection of urinary tract infection in childhood - Ben ghuzzi, Hunaydah (faculty of applied basic medical science - Libyan international medical university, 2022)
Urinary culture, Gram stain, and urine analysis assays were used in this investigation. "Leucocyte esterase, nitrate, Microscopy for bacteria, and pyuria" were tested in 100 children with signs of urinary tract infection. Goal was to compare the validity and benefits of a urinary Gram stain to a combination of Gram stain and total urine analysis, such as nitrate positireness , leukocyte esterase, bacteria microscopy, and white blood cell microscopy. Of 100 children (age: 2 days-15 years), 70% had a positive urinary culture : 43% boys and 57% girls . E. coli was the most commonly isolated agent (Escherichia coli) . The urinary Gram stain has a sensitivity and specificity of 80% and 83 percent, respectively, for both pyuria and Gram positivity. A positive urinary culture was found in 70 percent of 100 children (aged 2 days to 15 years): 43 percent of boys and 57 percent of girls . E .coli was the most commonly isolated agent (Escherichia coli) .The urinary Gram stain has a sensitivity and specificity of 80% and 83 percent, respectively, for both pyuria and Gram positivity . accounted for 42 percent and 90 percent of the whole urine analysis, respectively, while the entire urine analysis accounted for 3.5 percent. In symptomatic individuals, no urine screen can replace a urine culture, according to finding .
Keywords: UTI